Hydrodynamic force analysis of magnetite medium inside dense medium cyclone using multiphase GPU parallelized ASM model. (15th August 2021) - Kumar, Mayank; Mangadoddy, Narasimha; Banerjee, R.; Sreedhar, Gaekwad E.; Raparla, Shiv Kumar; Kumar, Rajan
Highlights: Study of medium segregation in DMCs using newly developed GPU based ASM model is made. Effect of inlet head, spigot diameter and feed RD on the forces acting on medium studied. Turbulence force analysis shows notable particle misplacement at smaller size particles. Lift forces predominant near the wall especially in the conical section of cyclone. GPU code is 13 times faster than the CPU code making DMC design exploration feasible. Abstract: In order to tackle the high compute cost of the multiphase simulations for dense medium cyclones, the development of an open source high fidelity LES based algebraic slip mixture multiphase flow solver is presented. The solver is parallelized on a general purpose GPU using a full load model, which provides around 13 times speed up as compared to a CPU implementation thereby, making design explorations using the current solver more feasible and less time consuming. The traditional ASM model was improved upon using more realistic slurry viscosity model and polydispersed hindered correlation for dense medium operation. The performance of the developed solver for dense medium cyclone operation was validated with the literature based gamma ray tomography (GRT) experimental results. The solver was then used to study the implication of variation in the key aspects of DMC operation such as pressure head, underflow diameter and feed particle concentration. The medium segregation is explained based on a novel non-dimensional force analysis of the drag, shear lift and turbulent dispersion. Finally, the response of the DMC in terms of hydrodynamic force analysis and density differential with the variation in design and operating variables has discussed. Based on the comprehensive force analysis of the medium a justification is provided as to why a lower pressure head is preferred for DMCs used in mineral processing.